Video-based smartphone app ('VIDEA bewegt') for physical activity support in German adults: a single-armed observational study. Issue 1 (25th January 2022) - Fischer, Tillmann; Stumpf, Paul; Schwarz, Peter E H; Timpel, Patrick
Abstract : Objectives: The primary objective of this study was to investigate the effect of the video-based smartphone app 'VIDEA bewegt' over eight programme weeks on physical activity in German adults. Design: The study used a single-arm observational design, assessing the app's effectiveness under real-life conditions. Data were collected from July 2019 to July 2020. Setting: The app is enabling users to access video-based educational content via their smartphone. A clinical visit or in-person contact was not required. Participants: All individuals registered in the freely available app were invited to take part in the study. Interventions: The app aims to increase physical activity in everyday life. It combines educative videos on lifestyle-related benefits and instructional videos of strength and endurance exercises to do at home with motivational components like goal setting, documentation of progress and personalised messages. Primary and secondary outcome measures: Primary outcomes were physical activity based one MET minutes per week (metabolic equivalent) and step numbers. Secondary outcomes included physical self-efficacy (motivational, maintenance, recovery self-efficacy), health-related quality of life: Mental Health Component Summary score and Physical Health Component Summary score. Results: Of 97 people included in the data analysis, 55 successfully completed the programme and all questionnaires. Significant increases over eight programme weeks (between T0 and T2) were observed in physical activity based on MET minutes per week, health-related quality of life, and recovery self-efficacy. Time spent sitting and body mass index significantly decreased for those completing the programme. Conclusions: Although significant benefits of physical activity were observed following a complete-case analysis, results should be dealt with caution. Studies with a larger and less heterogeneous sample and robust study designs able to measure causal effects would be desirable. Trial registration number: DRKS00017392.